2020
DOI: 10.21203/rs.3.rs-29743/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

S100A8 Promotes Inflammation via Toll-Like Receptor 4 After Experimental Traumatic Brain Injury

Abstract: Background: S100A8 is involved in the pathological processes of a variety of central nervous system(CNS) diseases related to inflammation including traumatic brain injury (TBI). However, the underlying mechanism for the induction of inflammation in the brain by S100A8 after TBI remains unclear, which was investigated in the present study.Methods: The weight-drop TBI model was used in this study. The mice were randomly assigned into 5 groups: the Sham, S100A8, S100A8 + TAK-242, TBI, and TBI + TAK-242 groups. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Targeting TLR4 signaling with the selective inhibitor TAK-242 (resatorvid) within hours of the injury reduces neuronal apoptosis and improves neurobehavioral impairments in rodents [64][65][66].…”
Section: Traumatic Injuriesmentioning
confidence: 99%
“…Targeting TLR4 signaling with the selective inhibitor TAK-242 (resatorvid) within hours of the injury reduces neuronal apoptosis and improves neurobehavioral impairments in rodents [64][65][66].…”
Section: Traumatic Injuriesmentioning
confidence: 99%
“…TAK‐242 can disrupt the interaction between TLR4 and the ligand, thereby inhibiting TLR4 signal transduction and its downstream signal activation [53, 54]. A previous study reported that TAK‐242 treatment alleviated S100A8‐induced neurological deficits and brain edema [20] also NF‐κB phosphorylation and proinflammatory cytokine production [29]. In the study about hypoxic–ischemic brain injury, NF‐κB signaling can regulate microglia‐mediated neuroinflammation [55].…”
Section: Disccussionmentioning
confidence: 99%
“…Sham rats were injected with 10 μl of normal saline. The process was performed following a previously reported method [20,29]. TAK-242 was intraperitoneally injected (3 mg/kg) 30 min before the injection of rS100A8 [20,29,30].…”
Section: Drug Administration To Animalsmentioning
confidence: 99%
See 2 more Smart Citations